2022
DOI: 10.1590/fst.45222
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids from Lagerstroemia speciosa (L.) Pers inhibits TNF-α-induced insulin resistance and inflammatory response in 3T3-L1 adipocytes via MAPK and NF-кB signaling pathways

Abstract: Adipocyte tissue inflammation orchestrates the occurrence and development of diseases induced by obesity. Here, the effects of Lagerstroemia speciosa (L.) Pers total flavonoids (LTF) on TNF-α-induced insulin resistance (IR) and inflammatory response in 3T3-L1 adipocytes and underlying mechanisms were studied. Cell glucose uptake test confirmed that TNF-α could induce IR in 3T3-L1 adipocytes. The sensitivity of 3T3-L1 adipocytes to insulin was increased by LTF treatment. The phosphorylation of IRS1 and Akt in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Studies showed that obesity-induced proinflammatory cytokines were closely related to insulin resistance [58,59]. However, in insulin-resistant individuals, a large number of proinflammatory cytokines and inflammatory mediators, especially TNF-α, MCP-1, and IL-6, were upregulated [60]. The current research illustrated for the first time that PC could significantly inhibit HFHF-induced inflammatory response, which was manifested in the reduction of inflammatory factors (TNF-α, IL-1β, and MCP-1) in serum and liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that obesity-induced proinflammatory cytokines were closely related to insulin resistance [58,59]. However, in insulin-resistant individuals, a large number of proinflammatory cytokines and inflammatory mediators, especially TNF-α, MCP-1, and IL-6, were upregulated [60]. The current research illustrated for the first time that PC could significantly inhibit HFHF-induced inflammatory response, which was manifested in the reduction of inflammatory factors (TNF-α, IL-1β, and MCP-1) in serum and liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are abundant in plant foods such as fruits, vegetables, tea leaves, and so on. Natural flavonoids have been proven in studies to be a class of chemicals with considerable anti-glioma efficacy, as well as low toxicity and side effects and excellent safety (Hardinasinta et al, 2022;Yin et al, 2022). Natural phytoflavonoids can suppress gliomas across the blood-brain barrier and can have a role in glioma resistance reversal.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, obesity has become a global epidemic in both developed and developing countries (Aleman et al, 2023;Geng et al, 2022). Obesity causes or exacerbates many health problems, both independently and in association with other diseases (Park et al, 2020;Yin et al, 2022). Obesity has been associated with the development of type II diabetes mellitus, coronary heart disease, an increased incidence of certain forms of cancer, and respiratory complications (Hwang et al, 2019;Santos & Sinha, 2021).…”
Section: Introductionmentioning
confidence: 99%